MELACAK AKAR RASIALISME DI INDONESIA DALAM PERSPEKTIF HISTORIS - Muntholib, Abdul (Faculty of Social Science, Universitas Negeri Semarang, 2008)
Chinese immigrant had settled in Indonesia long before the Europeans arrived, and quite significantChinese communities, engaged in commerce and mining enterprise, already existed before the 19th century.The most important factor was the region’s phenomenal economic development which offered opportunitiesthat were far more promising than in China. Chinese in Indonesia was minority; nevertheless they weremostly occupied in trade. This term, however, includes both commerce and industry, and covers everythingfrom peddlers to big businessmen. Contractual relations are increasing at the expense of trust relations;extreme individualistic competition, frugality, perseverance and the willingness to work long and hardare less emphasized than formerly, at least among the Peranakans. Historical evidence shows that mostly,Chinese businessmen build a good relationship with the state directly or indirectly, and if the currentcircumstance of Chinese prejudice arouse among the state, it could be the guidance to the depth of ruin.Keywords : Racialism, histories perspectives, ethnicity